Clinical features of acute generalized exanthematous pustulosis caused by hydroxychloroquine in rheumatology patients and exploration of CARD14 gene mutations - Luo, Feng; Yuan, Xue-mei; Xiong, Hong; Yang, Yu-zheng; Chen, Chang-ming; Ma, Wu-kai; Yao, Xue-ming (Frontiers in Medicine, 2023)
Introduction Acute generalized exanthematous pustulosis (AGEP) is a rare condition characterized by superficial pustules following drug ingestion or infection. Currently, there is no clear link between rheumatism and AGEP. It has been described that hydroxychloroquine (HCQ) is a rare cause of acute generalized epidermal necrolysis (AGEP). Presently, there are limited studies on HCQ-induced AGEP. We aimed to explore the clinical features and associated gene expression of AGEP induced after HCQ treatment exposure in rheumatology patients. Methods We assessed patients with HCQ-induced AGEP diagnosed at the Second Affiliated Hospital of Guizhou University of Chinese Medicine between January 1, 2017, and May 1, 2022. We also reviewed similar cases reported in specific databases. Results The study included five females (mean age, 40.2 years), and the mean time from initiation of HCQ treatment to symptom onset was 12.2 d. All patients received steroids and allergy medications after HCQ discontinuation, and the rash completely resolved within an average of 25.2 d. We performed whole exome sequencing and Sanger validation in our patient sample. CARD14 gene mutations were detected in three patients. Additionally, seven mutation sites were detected. Discussion HCQ-induced AGEP may have a longer latency period and regression time than AGEP induced by other drugs. Our patients all experienced CARD14 gene mutations. AGEP often resolves with topical therapy and drug discontinuation, although some cases require systemic steroid therapy. In the future, patients with rheumatism should pay attention to the effectiveness of HCQ during treatment and be aware of the associated skin toxicity.